2014
DOI: 10.2474/trol.9.71
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Carbonaceous Deposit Formation Caused by Lubricating Oil on High Temperature Metal Surfaces

Abstract: While formation of deposits in machinery used under high temperature conditions is inevitable, it needs to be minimized as much as possible. Desorption of deposits, though rarely reported, also needs to be addressed, as it could cause secondary damage. There have been a number of reports on the formation of high-temperature deposits and the effects of additives, none of which, however, addresses the desorption phenomenon as part of the deposit formation mechanism. Paying attention to the polar properties of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The dynamic viscosity of 70 °C–10/20 MPa–E2 is essentially the same as that of the feedstock, which will be discussed in section . In the thermal processing process, the ULO is more prone to deterioration in the presence of oxygenated and metallic compounds. , MCR results show that the problem of coking can be effectively avoided if the thermal processing is involved in the subsequent regeneration as a result of the removal of the heteroatom and heavy fraction from the feedstock.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic viscosity of 70 °C–10/20 MPa–E2 is essentially the same as that of the feedstock, which will be discussed in section . In the thermal processing process, the ULO is more prone to deterioration in the presence of oxygenated and metallic compounds. , MCR results show that the problem of coking can be effectively avoided if the thermal processing is involved in the subsequent regeneration as a result of the removal of the heteroatom and heavy fraction from the feedstock.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the conventional acid–clay method, while cost-effective and direct, employs concentrated sulfuric acid to react with asphaltenes and polar heteroatomic compounds . This process, however, gives rise to a considerable amount of acid sludge, leading to the corrosion of equipment. To circumvent the issues presented by acid treatments, solvent extraction methods were introduced, but these methods still necessitate solvent evaporation and high vacuum distillation, often resulting in significant coking and column fouling …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this plot, blend 6a containing 75% of crude oil A does not follow the tendency established by the other blends containing the same components. A similar behavior, an initial increase in the deposited mass followed by a decrease, has been reported in a previous study of the fouling in fuel oil upon adding a paraffinic oil . In this earlier study, different types of paraffinic oils were blended with the same fuel oil, and it was found that the deposit amount reached the maximum level when the ratios of paraffinic oil and fuel oil were the same.…”
Section: Resultsmentioning
confidence: 99%
“…A lower aniline point indicates the enhanced ability of an oil to dissolve polar substances, thereby helping to prevent accumulation of insoluble components and subsequent deposit formation. Dissolvability of deposits and their precursors in oil was also observed to be an important factor in deposit-formation tendency by Yokoyama et al [40]. When considering gas engine oil formulations, the deposit-formation tendency and solvency are not the only important factors.…”
Section: Formulation Considerationsmentioning
confidence: 95%